Smart grid communication-enabled intelligence for the electric power grid - Bush, Stephen F. (Chichester, West Sussex, United Kingdom John Wiley & Sons, Ltd, 2014)
"This book explores the smart grid from generation to consumption; both as it is planned today and how it will likely evolve tomorrow"-- Provided by publisher.
Includes bibliographical references (pages 493- 506) and index.
Keywords: Smart power grids